Fundamentals of Entrepreneurship (ENT300) : Saved haircut / Asrizal Hakim Othman … [et l.] - Othman, Asrizal Hakim; Collin, Davina Elvie; Angin, Evelyn Kurash; Muhidin, Saidatul Anisa; Dickie, Veronica Wilda (2019)
SAVED is a private male barber shop which is a serviced oriented that located in UiTM Kampus Samarahan 2, Kota Samarahan,94300, Sarawak. We provided services that allow male students and staff in UiTM get haircuts with affordable price that low than any price that any other competitors offered in Samarahan area. In our research found that students sometimes facing some financial crisis and also time management. So we provide this service that can be afforded by them to get a good haircut with a lower price because nowadays, it is hard to get a good haircut with lower price but we provided it here.